The stock market reaction to dividend reductions and omissions in China. Issue 3 (11th March 2019) - Dong, Jing; Li, Hui; Liu, Kerry; Wu, Xiaohui
Abstract : Purpose: The purpose of this paper is to investigate Chinese stock market reaction to the announcements of dividend reductions and omissions. Design/methodology/approach: The data sets cover the period from 1990 to 2009. A rolling portfolio approach is performed and the Fama–French three-factor model is used to calculate the post-announcement long-term abnormal returns. The matching method and the sub-sample tests are used to examine the robustness. Findings: After controlling for firm size, the unexpected earnings and government ownership, no evidence of the dividend announcement drift is found. The results also show that the government ownership and the large trading play a role in explaining the post-announcement abnormal returns. Originality/value: This is the first study concerning the Chinese market that examines the Chinese stock market reaction to dividend cut and omission using a long-time period of data.